KARAKTERISTIK PERTUMBUHAN JARAK PAGAR PADA MEDIA TANAH BEKAS PERTAMBANGAN BAUKSIT UNTUK PENGEMBANGAN DESAIN PEMBELAJARAN BIOLOGI - Firdaus L.N. '; Nursal ' '; Sulistiono ' ' (Biogenesis, 2014)
A field research has been conducted to observe the growth characteristics of PhysicNut (Jatropha curcas L.) cultivated on bauxite mined soil in the Biology NaturalLaboratory, Teacher Training and Education Faculty of the University of Riau,Pekanbaru. Parameters observed every single week include plant height, stemdiameter, and number of leaves, whereas at the end of the testing carried outmeasurements of leaf area, canopy dry weight, and root volume. The pH of the soilwas analyzed at the beginning and at the end of the test, while the temperature andhumidity were analyzed every single week. Growth characteristics were observedduring the 9-week period showed that the average height of Physic Nut plants reach42,9 cm and the relative growth rate (RGR) 3,40 cm/week. A mean diameter of 1,26cm rod with RGR 0.33 cm/week. The mean number of leaves around 9,78 cm 2 2,20RGR strands with strands/week. The total leaf area of Physic Nut directlyproportional to the volume of the dry weight of roots and canopy. The results of non-experimental studies can be utilized to improve the quality of teaching biology atSenior High School in the form of Syllabus development, Lesson Plan (LP), StudentAssignment Sheet (SAS) I and II, and Assessment Sheet. The review of the productdesign Syllabus, LP, SAS I and II, and Assessment Sheet shows that all the draftclassified Very Good, except for the Syllabus which was considered Good. In order tofind out the plant productivity in bauxite mined soil, the observation period in thisstudy can be extended to the generative phase. Meanwhile, to ensure the quality ofbiology learning design products, the testing steps still need to be followed up to thestage of Implementation and Evaluation.Keywords: Bauxite Mined Soil, Vegetative Growth, Jatropha curcas L., BiologyLearning Design, Physic Nut